Draft genomic DNA sequence of the facultatively methylotrophic bacterium Acidomonas methanolica type strain MB58. Issue 1 (6th January 2014) - Higashiura, Norie; Hadano, Hiromi; Hirakawa, Hideki; Matsutani, Minenosuke; Takebe, So; Matsushita, Kazunobu; Azuma, Yoshinao
Abstract Acidomonas methanolica (former name: Acetobacter methanolicus) is a unique acetic acid bacterium capable of growing on methanol as a sole carbon source. We reported the draft genome sequencing of A. methanolica type strain MB58, showing that it contains 3270 protein‐coding genes, including the genes involved in oxidation of methanol, such as mxaFJGIRSACKL and hxlAB, and oxidation of ethanol, such as adhAB and adhS.